Polymorphism Of The APM1 Gene In Subjects With Central Obesity Related To Lower High-Density Lipoprotein Cholesterol - Barliana, Melisa I (Diabetes Metab Syndr Obes, 2019)
BACKGROUND: Central obesity is a risk factor for metabolic syndrome. Subjects with central obesity have a higher risk of developing type 2 diabetes and cardiovascular disease. Many conditions affect the prevalence of central obesity, including energy expenditure, aging, proinflammatory conditions, and hormonal, genetic, and ethnic differences. Polymorphism of the APM1 gene, encoding the protein adiponectin, is closely related to metabolic syndrome. Adiponectin influences fatty acid oxidation and glucose intake in muscle. Therefore, variation in the APM1 gene is associated with diabetes and obesity. PURPOSE: The aim of the present study was to investigate the correlation of the single-nucleotide polymorphism (SNP) of the APM1 SNP rs2241766 with body mass index (BMI) and lipid profiles in Indonesian (Bandung) subjects. PATIENTS AND METHODS: Genotyping of the APM1 gene was performed using the Amplification Refractory Mutation System. Whole blood and serum of 54 subjects with central obesity (waist circumference [WC] ≥90 cm) and 53 healthy subjects (WC <90 cm) were collected. Measurements of the lipid profile (low-density lipoprotein [LDL], high-density lipoprotein [HDL], and total cholesterol [TC]) and BMI were examined. RESULTS: The TT and GT genotype were observed (no GG genotype) in all subjects. The TC, LDL, fasting blood glucose, and BMI did not show a significant correlation between genotype variations of APM1 with central obesity. Otherwise, subjects with central obesity with the TT genotype had lower HDL levels than those with the GT genotype (p = 0.014, significant OR 1.045; 95% CI). CONCLUSION: This finding suggests that the T allele of the APM1 SNP rs2241766 is dominant in the Bandung population, and subjects with the homozygous TT genotype have a higher incidence of metabolic disorder.